Pengembangan Modul Ajar Berbasis Flip HTML 5 pada Mata Pelajaran PDTM di Sekolah Menengah Kejuruan Negeri 2 Banda Aceh - Erlanda, Rendi; Yufrizal, Yufrizal (Lembaga Yasin AlSys, 2024)
This study aims to develop teaching modules in the form of learning modules at vocational schools in Banda Aceh. This research applies the R&D development model in the field of education in accordance with the 4D model reference which was carried out in FY 2022/2023 even semester. The 4D model steps include steps or stages which include, defining, designing, developing, and disseminating stages. Research data were obtained using a validation sheet in the form of a questionnaire. Data analysis used in the form of quantitative descriptive statistics, namely examining data by describing the data collected. The results of this module development research were declared feasible to be used as independent learning media for students, based on the results of the validity of the material experts obtained a final value of V of 0.842 and media experts of 0.909 with valid criteria. Based on the results of the assessment of the validity of the developed module, it can be concluded that the PDTM learning module for class X Machining Engineering developed is suitable for use as an additional learning medium for students.